Improvement Emotional Intelligence and English Language Ability Through Storytelling Activities in Elementary School Students Wajo District - Satriani; Bahri, Syamsul; Sadat, Anwar; Nurhidayanti; Khair, Ummul (Jurnal Pengabdian Kepada Masyarakat Patikala, 2022)
The goal of this Community Partnership Program activity is to increase children's emotional intelligence as well as their English skills. This is accomplished through the use of storytelling activities, with the fairy tales being told in English. The transmission of fairy tales in English is at the request of partners, as there are no English subjects in the 2013 curriculum. In reality, in this age of globalization, English is critical. Parents, particularly at wealthy institutions, are adamant that their children receive English classes, even if it is merely through extracurricular activities or extended school hours. An increase in children's emotional intelligence and English language abilities in elementary school kids is the goal to be met. Wajo Regency elementary schools are PKM partners. as well as the professional development provided to instructors to help them enhance their digital literacy skills. The teacher is expected to increase the quality of his or her instruction in this scenario. Most teachers solely utilized blackboards and markers to teach before the training. Teachers should be able to generate engaging digital-based teaching media as a result of this course. The availability of storytelling activities employing digital fairy tales in English has been achieved as a goal. as well as training in the creation of digital-based learning media, which was attended by roughly 60 teachers from Wajo Regency elementary schools. The teachers were successful in creating learning films, which resulted in a rise in children's emotional intelligence and students' English skills at partner schools.